Performative Analysis : Reimagining Music Theory for Performance - Swinkin, Jeffrey; Swinkin, Jeffrey (Book collections on Project MUSE., 2016)
A theory of musical interpretation. Analysis in the musical work ; Two interpretive roles -- Analytical essays. Schenkerian analysis as metaphor : Chopin, Nocturne in C minor, op. 48, no. 1 ; An analytical dialogue : Beethoven, String quartet in C minor, op. 18, no. 4, First movement ; Musical structure(s) as subtext : resisting Schumann's "Ring